2019
DOI: 10.1016/j.media.2019.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Fusing learned representations from Riesz Filters and Deep CNN for lung tissue classification

Abstract: A novel method to detect and classify several classes of diseased and healthy lung tissue in CT (Computed Tomography), based on the fusion of Riesz and deep learning features, is presented. First, discriminative parametric lung tissue texture signatures are learned from Riesz representations using a one-versus-one approach. The signatures are generated for four diseased tissue types and a healthy tissue class, all of which frequently appear in the publicly available Interstitial Lung Diseases (ILD) dataset use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Similarly, a total of 147 images are taken for testing in which each class has 21 images. Also, the efficiency of these classifier models is compared with DNN [9], CADx [11], MLP [13], CNN [16], and MIL [17] in terms of precision, recall, fmeasure, and accuracy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a total of 147 images are taken for testing in which each class has 21 images. Also, the efficiency of these classifier models is compared with DNN [9], CADx [11], MLP [13], CNN [16], and MIL [17] in terms of precision, recall, fmeasure, and accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…Joyseeree et al [11] suggested a new technique for classifying the different tags of infected and healthy pulmonary tissues from CT according to the concatenation of Riesz and deep features. Initially, discriminative parametric pulmonary tissue texture signs were trained from Riesz interpretations via a 1-vs.-1 method.…”
Section: Literature Surveymentioning
confidence: 99%
“…The method of sampling applied to fix the imbalanced data. [7] proposed to classify the tissues in lung. It aimed to detect and perform classification on lung disease based on the tissue in the lung.…”
Section: Literature Reviewmentioning
confidence: 99%
“…and (c) "fine-tuning" that aims to gradually train layers by tuning the learning parameters until a significant performance boost is achieved. Transfer knowledge via fine-tuning scenario demonstrated outstanding performance in chest X-ray and computed tomography image classification [12], [13].…”
Section: Introductionmentioning
confidence: 99%